EO-based indicators for biodiversity monitoring at national scale in Greece: framework development for the Hellenic biodiversity information system (EL-BIOS) (2024)
Giorgos Mallinis, Eleni Fitoka, Irene Chrysafis, Vangelis Fotakidis, Lena Chatziiordanou, Elena Chatzicharalabous, "EO-based indicators for biodiversity monitoring at national scale in Greece: framework development for the Hellenic biodiversity information system (EL-BIOS)," Proc. SPIE 13212, Tenth International Conference on Remote Sensing and Geoinformation of the Environment (RSCy2024), 132121K (13 September 2024); https://doi.org/10.1117/12.3038356